CT MYELOGRAPHY IN COMMUNICATING SYRINGOMYELIA - (:unkn) unknown (ELSEVIER SCI IRELAND LTD, 1991)
Although the etiology of syringomyelia is not clearly understood, many surgical methods have been proposed for its treatment. One widely used technique in cases of communicating syringomyelia is that of posterior fossa decompression and plugging of the obex (Gardner's Operation). In this paper we present five cases of syringomyelia which were investigated using detailed myelo-computerized tomographic techniques, of which two appeared to be communicating syringomyelia and which were treated by posterior fossa decompression and obex plugging. We also discuss the place of computed tomography in the differential diagnosis of communicating syringomyelia.
Keywords: COMPUTED TOMOGRAPHY HYDROMYELIA; SYRINGOMELIA; CT; COMPUTED TOMOGRAPHY SYRINGOMYELIA; COMPUTED TOMOGRAPHY MYELOGRAPHY